The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/rs13101952
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fishing Vessel Types and Analysis of Seasonal Activities in the Northern South China Sea Based on AIS Data: A Case Study of 2018

Abstract: In recent years, concern has increased about the depletion of marine resources caused by the overexploitation of fisheries and the degradation of ecosystems. The Automatic Identification System (AIS) is a powerful tool increasingly used for monitoring marine fishing activity. In this paper, identification of the type of fishing vessel (trawlers, gillnetters and seiners) was carried out using 150 million AIS tracking points in April, June and September 2018 in the northern South China Sea (SCS). The vessels’ sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The first stage is scheduled to commence commercial power generation in 2024, and the overall project will be completed and connected to the grid by the end of 2027. Due to the absence of freight ports in the vicinity of the FOWF region, as indicated by statistical data from the China Maritime Safety Administration's Automatic Identification System (AIS) [28], and in accordance with research findings by Wang [29,30], Wan [31], and Guan et al [32], it has been observed that within a 50 km radius around the FOWF, there is a lack of major shipping channels. The predominant vessels navigating in this proximity are several cargo vessels, and most of them are small and mid-sized fishing boats, as evidenced by the results presented in Table 3.…”
Section: Case and Site Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The first stage is scheduled to commence commercial power generation in 2024, and the overall project will be completed and connected to the grid by the end of 2027. Due to the absence of freight ports in the vicinity of the FOWF region, as indicated by statistical data from the China Maritime Safety Administration's Automatic Identification System (AIS) [28], and in accordance with research findings by Wang [29,30], Wan [31], and Guan et al [32], it has been observed that within a 50 km radius around the FOWF, there is a lack of major shipping channels. The predominant vessels navigating in this proximity are several cargo vessels, and most of them are small and mid-sized fishing boats, as evidenced by the results presented in Table 3.…”
Section: Case and Site Introductionsupporting
confidence: 54%
“…The analysis is confined solely to scenarios of collisions between fishing vessels and shipping fleets. Due to the lack of publicly available monthly statistics on the number of fishing vessels in various sea areas from Chinese official sources, this paper utilizes data for the months of April, June, and September published by Guan et al [32] in their research, with detailed data presented in Table 6. According to the data, the target sea area encompasses approximately 945,000 km 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Improvements are possible by combining AIS and remote sensing data to increase the effectiveness of fishing vessel activity monitoring. The enhanced monitoring will help in the implementation and monitoring of fishery policies [48][49][50][51]. Although AIS and remote sensing data can complement each other, further improvements may be possible through sub-regional scale studies, but it is difficult to find other data sources that can effectively complement AIS on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence of human‐induced and unspecified injuries in JM, SWH, and SNB could be linked to the different types and intensities of human activities at each location. For example, fishing activities differ among locations (Guan et al, 2021) and experience both seasonal (e.g., Chen et al, 2022; Guan et al, 2021; Li et al, 2021) and annual variations (Lin et al, 2021). These variations, and the fact that it is impossible to date injuries, make it hard to link injury prevalence with a specific time and activity level at a specific location.…”
Section: Discussionmentioning
confidence: 99%